Rheumatic manifestations of human immunodeficiency virus infection - Louthrenoo W. (2014)
PURPOSE OF REVIEW: To examine the rheumatic manifestations in patients with an HIV infection and the effect of antiretroviral therapy on the manifestation of the disease. RECENT FINDINGS: There has been decreasing prevalence of rheumatic manifestations since highly active antiretroviral therapy became available, but there appear to be new syndromes resulting from immune reconstitution. SUMMARY: Various rheumatic syndromes have been recognized in HIV-infected patients, including noninfectious inflammatory arthropathies, musculoskeletal infections, vasculitides, lupus-like syndrome, polymyositis, diffuse infiltrative lymphocytosis syndrome, and other uncommon rheumatologic conditions. Highly active antiretroviral therapy has caused dramatic changes in natural history, long-term outcome, morbidity and mortality in these patients. This is associated with the introduction of immune reconstitution inflammatory syndrome, particularly sarcoidosis, increased incidence of septic complications, and declining incidence of diffuse infiltrative lymphocytosis syndrome. © 2008 Lippincott Williams & Wilkins, Inc.